Active energy-efficient terahertz metasurfaces based on enhanced in-plane electric field density - Gupta, Manoj (2022)
Subwavelength confinement of electromagnetic modes in periodic structures is essential to tailor light−matter interaction in space and time. Metamaterials with strong electromagnetic field confinement can be extremely sensitive to surface conditions, thereby enhancing the metadevice response for low-energy electrical, thermal, and optical stimuli. It is important to note that the total field confinement matters, but the contribution of in-plane electric field density is critical to efficiently harness and manipulate light via active metasurfaces. The authors experimentally demonstrate a new planar metal–semiconductor hybrid terahertz (THz) metasurface design that shows highly sensitive active THz amplitude modulation towards optical illumination. In the proposed design, in-plane electric field density has been enhanced by 350% to lower the optical pump fluence requirement for energy-efficient, active modulation of resonances compared to the conventional inductive-capacitive resonant metamaterials. Such metasurfaces with large in-plane electric field density can find many applications in developing ultrasensitive sensors and active THz electrical and optical modulators operational at extremely low energies.